Bulgarian and Georgian Fictional Geographies and Coastscapes as Bridges for a Comparative Black Sea Literature - Ljuckanov, Jordan (Poznańskie Studia Slawistyczne, 2024)
The article drafts the notions of a spiritual-material landscape and of a coastscape amidst correlative notions like spiritualized material landscape, seascape, geography and cosmography. Against this theoretical context, it picks up a pair of literary works, one Bulgarian and one Georgian, that (re)shape regional marine imaginary on the levels of geography and of land-/sea-/coastscapes. It shows how they, in various degrees, model regional geography in the vein of alternative history. Both works are shown to “Levantinise” the life-worlds of their respective nations of extratextual origin, within a moderate move towards self-inclusion into a wider world and “westernisation”. The analysis of the pair charts a macroscopic typology and presupposes a history of alternative fictional geo-history and of metaliterature across the region. The comparison conveys a shared hesitation between a will for “archipelagic” experiencing of sea and for “thalassic” one.